PROMOTING STUDENTSâ CONCEPTUAL CHANGE ON THE CONCEPT OF ECOSYSTEM THROUGH PDEODE (PREDICT-DISCUSS-OBSERVE-EXPLAIN-DISCUSS-EXPLAIN) TEACHING STRATEGY - Nugraha, Ikmanda; Anggraeni, Sri; Amprasto, Dr. (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2016)
This study investigated conceptual change in studentsâ understanding of ecosystem concept. The PDEODE (Predict-Discuss-Explain-Observe-Discuss-Explain) teaching strategy, a variant of classical POE (Predict-Discuss-Explain) was implemented during the study. Sample was 28 senior high school students in one of senior high school in Bandung. Studentsâ ideas about ecosystem concept were revealed by a ten questions-test called ECT (Ecosystem Conceptual Test). Conceptual change in studentâs understanding of ecosystem concept was evaluated by administering ECT in pretest, posttest, and delayed posttest.Testsâ score were then analyzed quantitatively and qualitatively. One-way ANOVA test result showed statistically significant score difference (p<0.05) in each test which suggested PDEODE helped the students to achieve better understanding. Moreover, no statistically significant differences were found between posttest and delayed posttest scores, indicating that the teaching strategy helped the student to retain their new conceptions.ABSTRAKPenelitian ini menyelidiki perubahan konseptual pada pemahaman siswa tentang konsep ekosistem.Variasi dari strategi pengajaran POE (Predict-Discuss-Explain) yakni PDEODE (Predict-Discuss-Explain-Observe-Discuss-Explain) diterapkan selama penelitian ini. Sampel penelitian adalah 28 siswa di salah satu Sekolah Menengah Atas di Bandung. Ide-ide siswa tentang konsep ekosistem diungkap dengan menggunakan ujian 10 soal yang disebut sebagai ECT (Ecosystem Conceptual Test). Perubahan konseptual siswa dalam hal pema-haman tentang konsep ekosistem dievaluasi dengan ECT pada pretes, postes, dan delayed posttest. Hasil uji ANOVA satu arah menunjukkan nilai ketiga tes berbeda signifikan (p<0,05) yang menunjukkan bahwa PDEODE membantu siswa untuk memperoleh pemahaman yang lebih baik. Selain itu, tidak adanya perbedaan yang signifikan antara postes dan delayed posttest mengindikasikan bahwa strategi pengajaran ini dapat membantu siswa untuk mempertahankan pemahaman baru mereka.